Intersections of PTSD and DD: the evolution of PTSD symptom clusters throughout treatment of dissociative disorders - Abduragimova, Patricia (My University, 2017)
Despite phenomenological and neurobiological similarities between Post-Traumatic Stress Disorder (PTSD) and Dissociative Disorders (DD), and their frequent co-occurrence, they are rarely studied in conjunction with each other and PTSD symptom clusters are generally ignored. This study examines archival data from the Treatment of Patients with Dissociative Disorders (TOP DD) study to determine how PTSD symptom clusters differ in severity between DD patients in varying stages of treatment. I hypothesized that the Avoidance cluster would vary the least between Stage 1 and Stage 5 patients. Participants recruited by the TOP DD study researchers include 292 therapists and 280 patients diagnosed with DD. I conducted a MANOVA upon the three PTSD symptom clusters as Dependent Variables and the five stages of DD treatment as Independent Variables. As predicted, Avoidance showed the least variation between Stage 1 and Stage 5 of treatment, indicating that it may be the most resistant cluster to DD treatment.
(M.A.) -- Towson University, 2017